A Cross-Sectional Study on Cognitive Impairment of Alcohol Users among Residents of an Urban Area of Kancheepuram District, Tamil Nadu, India - Aravindh, Bhuvanesh; Swetha NB; Sujitha P (National Journal of Community Medicine, 2026)
Background: This community-based cross-sectional study assessed cognitive impairment among alcohol users in an urban setting in South India. Alcohol use disorder is frequently associated with cognitive impairment, which may adversely affect treatment engagement and functional outcomes. However, community-level evidence from urban Indian populations remains limited. The objective was to estimate the prevalence of cognitive impairment among alcohol users in the urban area of Kancheepuram district and to examine its association with the severity of alcohol use. Methodology: The study was conducted among 260 adult male alcohol users residing in the urban field practice area of a medical college in Anakaputhur, Tamil Nadu. Participants were selected through simple random sampling using the electoral list. Alcohol use severity was assessed using the Alcohol Use Disorder Identification Test, and cognitive function was evaluated using the Montreal Cognitive Assessment. Data were analyzed using bivariate and multivariable logistic regression methods. Results: Cognitive impairment was present in 30.8% of alcohol users in study population. Increasing severity of alcohol use was associated with worsening cognitive functioning, while higher age and lower educational attainment were associated with greater cognitive vulnerability. Conclusions: Cognitive impairment is a common finding among community-dwelling alcohol users and shows a clear association with alcohol use severity. Incorporating routine cognitive screening into community-based alcohol-related services may facilitate early identification and inform appropriate intervention strategies.